1994
DOI: 10.1017/s0022112094002661
|View full text |Cite
|
Sign up to set email alerts
|

Structure of turbulent boundary layers on smooth and rough walls

Abstract: The structure of turbulent boundary layers which develop with zero pressure gradient on a smooth wall and a k-type rough wall was examined using arrays of X-wires. Although the data were obtained only on two orthogonal planes, the technique provides some information on the three-dimensionality of the large-scale structures. The major effect of the roughness is to tilt the inclination of the structures towards the wall-normal direction. This is caused by the reduced damping of the wall-normal velocity fluctuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
108
4
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(144 citation statements)
references
References 24 publications
(41 reference statements)
30
108
4
2
Order By: Relevance
“…The current results are in line with previous findings on both smooth and rough walls investigations, which suggested similar values for the characteristic inclination of the packets [17,18,8,6,9,5,1,15,12]. On the contrary, the current results do not seem to suggest that the surface morphology can have a significant influence on the vortex packets inclination, certainly not to the extend some researchers have previously documented [11]. Also reported in figure 1.1 (b) are correlations of the wall-normal fluctuations, R v v .…”
Section: Resultssupporting
confidence: 91%
“…The current results are in line with previous findings on both smooth and rough walls investigations, which suggested similar values for the characteristic inclination of the packets [17,18,8,6,9,5,1,15,12]. On the contrary, the current results do not seem to suggest that the surface morphology can have a significant influence on the vortex packets inclination, certainly not to the extend some researchers have previously documented [11]. Also reported in figure 1.1 (b) are correlations of the wall-normal fluctuations, R v v .…”
Section: Resultssupporting
confidence: 91%
“…9a, the elongated contour of R uu is nearly aligned in the x-direction, while the contour of R vv is aligned in the y-direction. The yalignment of R vv was also noticed by previous studies in turbulent channel flow [12] and turbulent boundary layer flow over smooth and rough surface [13]. Further inspection of Fig.…”
Section: Separated Shear Flowsupporting
confidence: 83%
“…The authors attributed the apparent discrepancy to fundamental differences between channel and boundary layer flows. This conclusion was also reached by Bakken et al (2005) for similarly scaled roughness over a range of Re τ , as well as by Volino, Schultz & Flack (2007), whose correlations showed no evidence of structural differences between the boundary layers over a smooth wall and a mesh-roughened wall geometrically similar to that of Krogstad & Antonia (1994) with k/δ = 1.4 %. Flack, Schultz & Shapiro (2005) also showed that outer scaling was satisfied in a boundary layer for velocity statistics up to the third order for k/δ 6 2.2 %.…”
Section: Introductionmentioning
confidence: 63%
“…Krogstad, Antonia & Browne (1992) compared the boundary layer developed over a smooth wall with that developed over a wall roughened by a wire mesh with k/δ ≈ 2.1 %: they found a significant increase in the wall-normal turbulence intensity, v 2 , through the outer layer, as well as an increase in the frequency and magnitude of sweep and ejection events. Krogstad & Antonia (1994) later demonstrated that these observations could be attributed to a rotation of the large-scale structure towards the wall-normal axis relative to the smooth-wall case. These observations were corroborated by the particleimage velocimetry results of Keirsbulck et al (2002) and the direct numerical channel simulations of Bhaganagar, Kim & Coleman (2004), with k/δ = 3.8 and 5.4 %, respectively.…”
Section: Introductionmentioning
confidence: 93%